ANALISIS YURIDIS BENTUK KEWAJIBAN ATAS PELAKU TINDAK PIDANA PENAMBANGAN TANPA IZIN (STUDI PUTUSAN NOMOR 168/PID.SUS/2017/PN Pli ) - Evi Retno Wulan; Andre Abadi Santoso (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Abstract: In mining behavior that does not have a permit, in essence it has fulfilled elements that can be threatened with criminal law as stipulated in the provisions of Article 158 Law Number 4 of 2009 concerning Mineral and Coal Mining. The problem in this research is how the form of criminal liability for business actors who carry out mining business without IUP, IPR, or IUPK in the case study of decision number 168/Pid.Sus/2017. The research method used is an analytical method used to collect data by means of a literature study. This type of research includes normative juridical research. That is, legal research materials were obtained qualitatively normatively. Based on all the legal facts, it was revealed that M. Riduan who committed the criminal act of mining without a business license could be asked for criminal liability or responsibility because he met the requirements to be held criminally responsible. Therefore, the Honorable Panel of Judges sentenced the defendant M. Riduan to 10 months in prison and a fine of Rp. 10,000,000,000 with a subsidiary of 2 months in prison. That the defendant has fulfilled all the requirements to be asked for criminal liability or responsibility, so the judge in imposing a sentence on the perpetrator of the criminal act of mining without a permit must consider mitigating and aggravating factors so that the sentence imposed is in accordance with the criminal act of the defendant.